Applications of Molecular Markers in Fruit Crops: A Review - Goswami, Manika; Attri, Kaushal; Goswami, Isha (International Journal of Economic Plants, 2022)
Markers are any trait of an organism that can be identified with confidence and relative ease, and can be followed in a mapping population or they can be defined as heritable entities associated with the economically important trait under the control of polygenes. Molecular markers have diverse applications in fruit crop improvement, particularly in the areas of genetic diversity and varietal identification studies, disease diagnostics, hybrid detection, sex differentiation and marker assisted selection. Molecular markers provide new directions to the efforts of plant breeders particularly in gene localization, taxonomy, phylogenetic analysis and also play an important role to decrease the time required for development of new and excellent cultivars. The most interesting application of molecular markers is marker-assisted selection (MAS). Suitable DNA markers should be polymorphic in the nature and should be expressed in all tissues, organs, at various developmental stages. Compared with traditional breeding programs, molecular markers can increase the efficiency and effectiveness of fruit breeding programs.